Culturally Informed Neuropsychological Evaluations in Pediatric Epilepsy: Evidence-Based Practice Considerations. (29th March 2023) - Berrios-Siervo, Gretchen M; Salinas, Christine M; Bender, H Allison; MacAllister, William S; Vega, Clemente; Boada, Richard; Strutt, Adriana M; MacDonald, Beatriz
Abstract: Objective: Epilepsy is one of the most common reasons for referral for a pediatric neuropsychological evaluation due its high prevalence in childhood and our well-established clinical role in tertiary care settings. Emerging evidence indicates that racial and ethnic minority populations experience increased epilepsy burden compared with White peers. Although there has been heightened recognition in our specialty regarding the dire need for culturally and linguistically responsive evaluations, the scientific evidence to support effective neuropsychological service delivery for bi/multilingual and bi/multicultural youth with epilepsy is comparatively scant and of poor quality. As a result, significant patient and clinical challenges exist, particularly in high stakes presurgical pediatric epilepsy evaluations of bi/multilingual and bi/multicultural children. Method: Given that Spanish is the most common language spoken in the United States after English, this paper will focus on Spanish and English measures, but will provide evidence-based practice considerations that can inform practices with other non-English speaking communities. Cultural and linguistic factors that affect clinical decision-making regarding test selection, test interpretation, and feedback with families are highlighted. Results: We offer a review of neuropsychological profiles associated with pediatric epilepsy as well as a flexible, multimodal approach for the assessment of linguistically and culturally diverse children with epilepsy based on empirical evidence and the clinical experiences of pediatric neuropsychologists from diverse backgrounds who work with children with epilepsy. Conclusion: Limitations to this approach are discussed, including the lack of available measures and resources for culturally and linguistically diverse pediatric populations. A case illustration highlights a culturally informed assessment approach.